Penerapan Standar Akuntansi Keuangan pada UMKM Kopitisi dan Fandi Laundry di Kota Yogyakarta - A. Shafa Sahra Kamila; Tutut Dewi Astuti (Universitas Katolik Widya Karya Malang, 2024)
Field Work Practice (PKL) activities are implemented to help UMKM perpetrators in accounting and financial reporting in accordance with the methods of SAK EMKM. The activities are carried out at the Kopitisi and Fandi Laundry enterprises located in Yogyakarta. The writing method used is quantitative descriptive. Activities begin with survey of activity objects, activity planning, activity implementation, evaluation, and activity reporting. As a result of this activity, the owners of the company Kopitisi and Fandy Laundry have been able to make financial statements in a simple and good way so that they can be applied in their monthly accounts.